Two new species of Dendrobrachia Brook, 1889 (Cnidaria: Octocorallia: Dendrobrachiidae) from the north-eastern Atlantic and western Mediterranean - Lopez-Gonzalez, PJ (2012)
Examination of recent benthic material collected during several cruises in the Gulf of Cadiz (NE Atlantic) and the Strait of Sicily (Mediterranean) has allowed the taxonomic reassessment of some previously identified specimens belonging to the monogeneric gorgonian family Dendrobrachiidae Brook, 1889. Dendrobrachia fallax Brook, 1889 is the type species of the single genus in this family, and was originally described from Ascension Island (South Atlantic). Subsequently, other authors reported the presence of this species in Cape Verde Islands (north-eastern Atlantic) and some Mediterranean localities (Alboran Sea and the Strait of Sicily). The study of the specimen from the Prince of Monaco collections in Cape Verde Islands, and recently collected material from the Gulf of Cadiz (north-eastern Atlantic) and in the south of Malta (Mediterranean), materials previously considered as D. fallax, allow us to recognize two undescribed species in this genus. All previous records of D. fallax from the north-eastern Atlantic and Mediterranean should be considered incorrect. Opresko and Bayer (1991) added two additional species of Dendrobrachia. Two new species are described here and compared with their congeners.